2006
DOI: 10.1165/rcmb.2005-0473oc
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Oxidative Stress in the Lungs of Cystic Fibrosis Transmembrane Conductance Regulator Protein Mutant Mice

Abstract: Cystic fibrosis is a fatal genetic disorder involving dysfunction of the cystic fibrosis transmembrane regulator protein (CFTR) resulting in progressive respiratory failure. Previous studies indicate that CFTR regulates cellular glutathione (GSH) transport and that dysfunctional CFTR is associated with chronic pulmonary oxidative stress. The cause and the source of this oxidative stress remain unknown. The current study examines the role of the mitochondria in CFTR-mediated pulmonary oxidative stress. Mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 61 publications
6
69
1
Order By: Relevance
“…Mitochondrial GSH levels have also been reported to be lower in both lung cells from CFTR knock out mice and nonCF mice and also in cultured human CF (IB3) vs. CFTR-corrected (C38) cells (59). In contrast, the present data showed no differences in mitochondrial redox potentials between CF and CFTR-corrected cells.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…Mitochondrial GSH levels have also been reported to be lower in both lung cells from CFTR knock out mice and nonCF mice and also in cultured human CF (IB3) vs. CFTR-corrected (C38) cells (59). In contrast, the present data showed no differences in mitochondrial redox potentials between CF and CFTR-corrected cells.…”
Section: Discussioncontrasting
confidence: 61%
“…Hypoxia like that observed for CF airway epithelial cell cultures is known to increase mitochondrial production of ROS (50,15,16,51), and recent measurements of mitochondrial GSH and DNA oxidation have given indications that CF mitochondria are oxidized compared to nonCF (17). However, experiments using roGFP1 here showed that adenoviral expression of CFTR did not alter redox regulatory properties of the cell surface, mitochondria, cytosol or ER.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The cells were lysed with a sonicating probe (Cole-Parmer Instruments, Vernon Hill, IL), and lactate dehydrogenase activity was determined in both media and lysate samples. To measure toxicity, the percent of total lactate dehydrogenase release was utilized as described previously (22). Cell lysate protein values were used to normalize GSH values and were determined spectrophotometrically with the Coomassie Protein Assay kit according to the manufacturer's protocol (Pierce).…”
Section: Methodsmentioning
confidence: 99%